Metal Organic Frameworks Modified Proton Exchange Membranes for Fuel Cells - Liu, Quanyi; Li, Zekun; Wang, Donghui; Li, Zhifa; Peng, Xiaoliang; Liu, Chuanbang; Zheng, Penglun (Frontiers in Chemistry, 2020)
Proton exchange membrane fuel cells (PEMFCs) have received considerable interest due to their low operating temperature and high energy conversion rate. However, their practical implement suffers from significant performance degradation due to the limitation of moisture content. In particular, proton exchange membrane (PEM) as the core component of PEMFCs, have shown a strong correlation between its properties (e.g. proton conductivity, dimensional stability) and the performance of fuel cells. Recently, various metal-organic frameworks (MOFs), a novel type of organic-inorganic nanocomposite material, have demonstrated their great potential to improve the proton conductivity of PEMs. The recent progress in the modification of proton exchange membranes with MOFs is reviewed and discussed in this paper, with special focus on the improvement of proton conductivity of composite membrane. To conclude, the challenges and perspectives in this fields are also provided.